MECHANISM OF IMMEDIATE JUDICIAL REVIEW AFTER DETENTION AT THE INVESTIGATION STAGE: A HUMAN RIGHTS PERSPECTIVE - M. Rizki Yudha Prawira (Program Studi Hukum Tata Negara Islam, Fakultas Syariah, Universitas Islam Negeri (UIN) Datokarama Palu, 2025)
This study examined the provisions on detention during the investigative process as a coercive measure under the Draft of Criminal Procedure Code (RKUHAP). These provisions are deemed not fully aligned with the International Covenant on Civil and Political Rights (ICCPR) and its official interpretation in General Comment No. 35. The research employs a normative juridical methodology with a comparative approach, analyzing national legal norms against international standards. The findings reveal that the RKUHAP's detention provisions do not fully adhere to international human rights principles, particularly the state's obligation to prevent prolonged detention without independent judicial oversight. The principle of